Energy-efficient quality of service aware forwarding scheme for Content-Centric Networking. (December 2015) - Li, Chengming; Liu, Wenjing; Wang, Lei; Li, Mingchu; Okamura, Koji
Abstract: Content-Centric Networking (CCN), which changes from host-centric communication model to content-centric communication model, has recently attracted a lot of attention from researchers. As recently emerged a clean slate approach of the future Internet, CCN needs to be further supplemented yet. Since power consumption by Internet and user demand for Quality of Service have been increasing year by year, one of the major challenges in CCN is how to support an energy-efficient intelligent forwarding engine. To address this challenge, this paper proposed a Greening Domain and Ant Colony based Forwarding (GDACF) scheme which is a joint caching and forwarding strategy. In our proposals, we firstly use popularity inspired caching and adaptive rate methods to reduce power consumption of CCN; Then we design an ant colony based packets forwarding scheme to support Quality of Service for CCN. The evaluation results show that our proposals decrease data retrieve time from 3.29% to 16.16% and save energy from 9.66% to 15.08% compared with original CCN forwarding strategy. Abstract : Highlights: We consider joint caching and forwarding methods to reduce power consumption. We used Popularity Heuristic caching and Adaptive link rate for energy-efficiency. We proposed an Ant Colony based Interest forwarding method for Quality of Service.